BIOCHEMICAL ANALYSIS FOR EXPLORATION OF TOXICITY OF ARSENIC (The Research of Medical Science Review, 2025)
Arsenic is a natural metalloid which is present in the universe everywhere. Poisoning of arsenic is major issue that affects different species. Current study was performed to investigate the toxic effects of feeding inorganic heavy metals such as arsenic on important organs of body such as Liver, kidney, muscle and brain of common quail. Total 120 birds were purchased from the market.60 birds were used in winter and 60 in spring trial. These divided into three groups one kept as control, second group was given (low concentration @ 1.5mg) and third group received are (high concentration @ 2.5mg) of arsenic .Conclusions: Clinical signs including diarrhea, appetite loss and decrease in body weight was observed in all treated groups and control group birds gain weight. Histoptahologoical examination of different tissues, In Liver, revealed the congestions, pyknosis and cytoplasmic vacuolation were main histopathological changes observed in liver. In kidney histopathological changes observed were swelling of tubular epithelium and destruction of blood cells. In brain changes observed was reduction of granular layer and purkinji cell layer not present. In Muscles Absence of nucleus in few mayo fibers occurred. The current study that arsenic causes the severe toxicity in body organs (Liver, kidney, muscle, brain) of birds.